Firm Accommodation After Workplace Disability: Labor Market Impacts and Implications for Subsidy Design - Aizawa, Naoki; Mommaerts, Corina; Rennane, Stephanie (Econometrica, 2026)
This paper studies the labor market impacts of firm accommodation decisions after workplace disability and assesses implications for the design of firm subsidies. We leverage a workers' compensation (WC) program in Oregon that provides wage subsidies to firms for accommodating workers with workplace disabilities. Leveraging rich administrative data and a policy change to the wage subsidy, we show that accommodation rates respond to the subsidy rate and that receipt of accommodation leads to a significant increase in employment and earnings a year later. To explore welfare implications, we develop and estimate a frictional labor market model of accommodation as a form of human capital investment. Worker turnover and imperfect experience rating in WC lead to underaccommodation and inefficient labor market outcomes after workplace disability. Counterfactual simulations show that subsidizing accommodation not only improves long‐run labor market outcomes of workers experiencing work‐related disability but also yields welfare gains for most workers.